The Changes in the Endothelial Function and Haemostatic and Inflammatory Parameters in Subclinical and Overt Hyperthyroidism. (3rd December 2013) - Popławska-Kita, Anna; Siewko, Katarzyna; Telejko, Beata; Modzelewska, Anna; Myśliwiec, Janusz; Milewski, Robert; Górska, Maria; Szelachowska, Małgorzata
Abstract : Introduction . The aim of the present study was to compare the levels of circulating markers of endothelial function and low-grade inflammation in patients with subclinical and overt hyperthyroidism (OH) due to Graves disease (GD) and toxic nodular goiter (TNG). Material and Methods . The group studied consisted of 42 patients with GD, 75 patients with TNG, and 39 healthy controls. Results . Circulating markers of endothelial dysfunction were elevated in the patients with both SH and OH, but the concentrations of interleukin-12 (IL-12) (P < 0.05 ), IL-18 (P < 0.05 ), fibrinogen (P < 0.01 ), and von Willebrand factor (vWF) (P < 0.05 ) were significantly higher in the OH than in the SH group. The highest levels of IL-6, IL-12, IL-18, vWF, sVCAM-1, and fibrinogen were found in the patients with GD, but the differences between the GD, and TNG groups were not significant. In the subjects with OH serum IL-6 was positively associated with FT3 (R = 0.276, P < 0.05 ), FT4 (R = 0.273, P < 0.05 ), and thyroid peroxidase antibodies (R = 0.346, P < 0.01 ) levels. Conclusion . Our results may suggest that both SH and OH may be associated with endothelial dysfunction, which is reflected by decreased fibrinolytic activity, hypercoagulability, and increased levels of IL-6, IL-12, and IL-18 and depends not only on the cause but also on the degree of hyperthyroidism.